Design and drafting profile of ship propeller by using AutoCAD - AutoLISP / Marzuki Maarof and Ahmad Rizal Abu Kassim - Maarof, Marzuki; Abu Kassim, Ahmad Rizal (1993)
This project ( thesis ) is to develop a computer system in term of programming using AutoLISP and produce the geometrical modelling for propeller profile by using AutoCAD. In the actual design process of propeller, many considerations have been taken to determine values which can be standardized. Taking the Netherlands Ship Model Basin for propeller series B, program is written in AutoLISP that includes of input data ( from the standard ) and calculation process. The flow of the program is only concentrated on types of propeller profile, which can be assumed as neglecting all engineering aspects. AutoCAD act as a compiler of the AutoLISP program. Besides that, the program also consists of AutoCAD built-in command as a support to produce the modelling profile either in screen monitor or hard copy. Points, which are generated by the program, would then be used in mesh modelling process to produce the flexible size profile on screen.